Expression of glucose transporter 1 in human endometrial and decidual tissue - Strowitzki, Thomas; Capp, Edison; Wolff, Michael von; Müller-Höcker, Josef (Gynecological endocrinology, 2009)
Regulation of endometrial glucose transport is important for the decidualization process. Therefore ,we have examined the expression of the glucose transporter protein isoform 1 (GLUT1) in endometrial samples during the menstrual cycle and in decidual tissue by immunohistochemistry ,and GLUT1 mRNA by RNase protection assays. GLUT1 protein was not detected in proliferative endometrial samples ,but was highly expressed in decidual tissue. Placental tissue was highly positive. GLUT1 mRNA could be detected in endometrial samples with an increase in endometria of the late secretory phase (day 25-28) and maximum concentration in the decidua of the 9th-10th week of gestation. Our results show that GLUT1 is differentially expressed in the different phases of the human endometrium with a maximum in the human decidua. Therefore ,GLUT1 may be an important marker for endometrial differentiation.
Published online: 28 Aug 2009
Gesehen am 25.11.2020